2008
DOI: 10.1063/1.2998825
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of organic solar array for applications in microelectromechanical systems

Abstract: We have developed an innovative way to fabricate organic solar arrays for application in dc power supplies for electrostatic microelectromechanical systems devices. A solar array with 20 miniature cells interconnected in series was fabricated and characterized. Photolithography was used to isolate the individual cells and output contacts of the array, whereas the thermal-vacuum deposition is employed to make the series connections of the array. With 1mm2 for single cell and a total device area of 2.2cm2, the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…10 The highest PCE of 0.44% was achieved after 16 min of annealing, which is significantly better than previously reported values for high-voltage polymer cells. 2,6 Further annealing decreased the PCE to 0.31%, but V OC increased steadily to reach 89.6 volts after 80 min. This increase in V OC with thermal annealing is reproducible and had been observed for cells with different thicknesses of the Al cathode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The highest PCE of 0.44% was achieved after 16 min of annealing, which is significantly better than previously reported values for high-voltage polymer cells. 2,6 Further annealing decreased the PCE to 0.31%, but V OC increased steadily to reach 89.6 volts after 80 min. This increase in V OC with thermal annealing is reproducible and had been observed for cells with different thicknesses of the Al cathode.…”
Section: Resultsmentioning
confidence: 99%
“…These solar cells were fabricated from amorphous silicon, and achieved voltages above 100 volts by connecting miniaturized cells in series. 1 Recently, a high-voltage polymer solar cell fabricated from a blend of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl-C 61 butyric acid methyl ester (PCBM) has been demonstrated by Niggemann et al 2 The P3HT:PCBM system represent one of the most promising material sets for organic solar cells, achieving efficiencies of around 5%. 3 Application of organic semiconductors for high-voltage solar cells has the advantage of potential low-cost roll-to-roll fabrication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are commonly created by chemical synthesis, including cation exchange [ 1 , 2 , 3 ] and hydrothermal method [ 4 , 5 ]. Nanorods would have great applications in display technologies [ 6 , 7 ], micro-electro-mechanical systems [ 8 , 9 , 10 , 11 ], cancer therapy [ 12 , 13 ], energy harvesting [ 14 , 15 ], light-emitting devices [ 16 , 17 ], and solar cells [ 18 , 19 , 20 ]. Any defect in nanorods during their synthesis or after that may limit their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Various fabrication approaches for producing serially interconnected organic solar cells have been demonstrated. Lewis et al demonstrated a high-voltage organic solar array with miniature cells interconnected in series [8]. Top electrodes were deposited and patterned through a shadow mask for making the series connections of the array.…”
Section: Introductionmentioning
confidence: 99%